Research ethics to consider when collecting oral histories in wilderness areas such as the Kruger National Park - Schellnack-Kelly, Isabel S. (HTS teologiese studies, 2022)
In the last half century, oral history has emerged as a historical approach that is being considered by archivists involved with the collection and accessibility of archival collections for researchers and interested members of the public. The approach to ethics by oral historians has emerged from two major fears: the fear of failing as researchers and the fear of failing the narrators and doing harm. Archivists also need to be cognisant of these fears when collecting oral history. Confronting these fears makes it possible to understand the complex questions behind oral historians’ and archivists’ preoccupations and sheds light on how oral history has evolved and expanded as a field. The research objectives of this article are to determine the three principles identified from the Belmont Report that relate and should be applied to the collection of oral histories by archivists and historians from communities and individuals residing and working in and alongside the Kruger National Park. The theoretical framework for this article is the critical race theory to address historical accounts from communities and individuals sidelined by the mainstream media in South Africa. For the purposes of this article, the study was conducted with the Makuleka and Tsonga communities to determine what ethical implications need to be respected when conducting oral history projects with communities.Contribution: This article will contribute to ethics concerning social sciences and specifically the collection of oral history.